Laparoscopic approach for a presacral myelolipoma resembling a liposarcoma. Issue 7 (11th July 2018) - Rizzo, G; Coramusi, C; Pietricola, G; Sionne, F; Castri, F; Pafundi, D P; Aversa, R; Coco, C
Abstract: Myelolipomas are rare benign tumors that are commonly found in the adrenal glands. Extra-adrenal locations are rare, and presacral myelolipomas represent the most common extra-adrenal location. The differential diagnosis of malignant presacral neoplasms is very challenging. We present a case of a presacral neoplasm that was completely removed with a laparoscopic approach and diagnosed as a myelolipoma only after pathological examination.